Eugenics of inequality: UK and US fatherhood premia across the earnings distribution, 1974-2010 - Lynn Prince Cooke (Luxembourg Income Study (LIS), 2014)
Fathers in many countries enjoy a wage premium as compared with childless men, but parenthood does not benefit all men equally. Income inequality among men has increased markedly since the 1970s, suggesting that differences among fathers have grown over time. Five waves of LIS data and regressions of the recentered influence function are used to compare the unconditional quantile partial effects of children along UK and US men's earnings distributions. In the 1970s, most UK and US fathers enjoyed a modest premium regardless of their relative earnings, which decreased as number of children increased. This bonus was not attributable to household specialization in paid work, as once controlling for partnership, wives' earnings did not significantly alter the fatherhood premium for most men. Since the 1970s, a more eugenic structure has emerged. Net of human capital and labor supply, the lowest-earning fathers in both countries face penalties. UK fathers' premia across the remainder of the distribution are similar. In contrast, US fathers' premia continue to increase as earnings increase, which translates into ever-greater absolute fatherhood bonuses for the most-privileged US men.
Keywords: 330; earnings; inequality; parenthood; international comparisons; Männliche Arbeitskräfte; Eltern; Lohn; Lohnstruktur; Großbritannien; USA